Teacher agency, linguistic diversity, and everyday multiculturalism appropriating MTB-MLE policy in Bongao, Tawi-Tawi - Colicol, Fernigil L.; Camposano, Clement C.; Arzadon, Maria Mercedes E.; Lagarto, Ana Raissa T.; Reoperez, Marie Grace C.; Javiniar, Joel C.; Aguja, Mario J. (Quezon City College of Education, University of the Philippines Diliman, 2024)
Informed by anthropology and sociology of education, this ethnographic study aimed to foreground teacher agency in the language-in-education policy by exploring how it was achieved in the Mother Tongue Based-Multilingual Education (MTB-MLE) implementation by the teachers at the Mindanao State University Integrated Laboratory School (MSU-ILS) in Bongao, Tawi-Tawi, a linguistically diverse and conflict-affected province in the Bangsamoro, Philippines. Specifically, it focused on (a) the contextual factors in language use, (b) the teacher agency, and (c) the consequences of teacher agency in the MTB MLE implementation.

I engaged eight MTB-MLE teachers and two assistant principals as key actors from the MSU-ILS Standard Basic Education Curriculum (SBEC) and the MSU-ILS Standard Madrasah Education Curriculum (SMEC) in my school observations, interviews, and focus group discussions. Moreover, I reflected on my 11-year stay in Tawi-Tawi alongside a wide range of secondary sources. I analyzed my ethnographic data iteratively based on my research framework and literature. Thematic analysis involving creating codes, subthemes, and themes was used.

The study revealed a disadvantaged context constrained the MSU-ILS MTB-MLE teachers’ agency. Inadequate support from above, side, and other below actors, and the top-down policy limited literacy in the official medium of instruction. Sidelining identity and cultural diversity as components of MTB-MLE restricted teacher agency further. Nevertheless, teachers demonstrated everyday multiculturalism and appropriated MTB-MLE. Operating beyond the policy, such as teachers' using an unauthorized language to deliver instruction effectively, suggests that teacher agency played out actively at the below level and, hence, crucial in the language-in-education policy.
Dissertation
Includes bibliographical references (209-231 leaves)
Keywords: Mindanao State University Integrated Laboratory School; Mindanao State University Tawi-Tawi. College of Technology and Oceanography; Native language and education -- Philippines -- Bongao (Tawi-Tawi).; Multilingualism -- Philippines -- Bongao (Tawi-Tawi).; Language policy -- Philippines -- Bongao (Tawi-Tawi).; Multiculturalism -- Philippines -- Bangsamoro Autonomous Region in Muslim Mindanao